Permanent Sensorineural Deafness in a Patient with Chronic Myelogenous Leukemia Secondary to Intracranial Hemorrhage - Sakshi Kapur; Michael Wax; Levin Miles; Adnan Hussain (Case Reports in Hematology)
A 52-year-old male presented with tinnitus and fullness in left ear for one day. Workup revealed a white blood cell count of 685×103/μL with marked increase in granulocyte series and myeloid precursors on peripheral smear. The initial impression was chronic myelogenous leukemia with hyperleukocytosis, and patient was started on hydration, hydroxyurea, and allopurinol. Patient tolerated bone marrow biopsy well but continued to bleed excessively from the biopsy site. Results confirmed Philadelphia chromosome positive chronic myelogenous leukemia (chronic phase). On day three of hospitalization, patient developed sudden slurred speech along with shaking movements involving extremities. Magnetic resonance imaging revealed multiple hemorrhages throughout the brain. Hydroxyurea was continued until insurance coverage for nilotinib was getting approved. On day nine of hospitalization, patient developed sudden bilateral sensorineural deafness. Repeat magnetic resonance imaging revealed multiple new hemorrhages throughout the brain. Computer tomography of the temporal bones showed inflammatory changes in right and left mastoid cells. Nilotinib was started on day eleven of hospitalization. Patient’s white blood cell count continued to decrease, but there was no improvement in hearing. Four months later, patient was treated with bilateral transmastoid cochlear implants. This case highlights permanent deafness as a hemorrhagic complication secondary to chronic myelogenous leukemia.